IMPORTANT FACTORS FOR MORE EFFECTIVE LEARNING OF MATHEMATICS - Cunska, Aija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Mathematics is an important and complex subject, and research in the field of neuroscience shows that 50% of people have a fear of mathematics. However, it is a subject that students will need for the rest of their lives. Educators recognize that every student needs an individual approach, but the teaching methods are still the same for the whole class. The poor results in mathematics also suggest that students' perceptions and interests have changed, and that old teaching methods are no longer as effective as before and that new solutions need to be invented. The aim of the research is to identify important factors that are necessary for more effective learning of mathematics in general education schools. Qualitative research methods were used for the research strategy - in-depth interviews, focus group discussions, surveys of pupils and students, information analysis in the media, pedagogical and business experience, as well as world success stories. As a result of the research, the following have been identified: 1) problems that were identified using the distance learning during the Covid19 pandemic; 2) students' wishes that arouse interest in mathematics; 3) the interests of students, which indicate the need for interdisciplinary approaches; 4) advantages of artificial intelligence (AI) in education. The study points to the necessity for collaboration between educators, industry professionals, entrepreneurs and researchers, and for AI solutions to create deeper, faster and more personalized learning of mathematics in general education schools in the future, increasing the growth of every student.